(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study describes farm management practices, determines farmers’ knowledge of Salmonella, and identifies agricultural extension advisory services available to strengthen livestock farmers to examine the prevalence of Salmonella outbreaks among poultry farms in Osun and Ogun, Nigeria. The study utilized a cross-sectional survey of 240 poultry farmers and 60 agricultural extension workers from both states. Data was collected with an interview schedule and analysed using percentages, frequency count and mean. Results indicate that the majority (68.3% and 67.5% in Osun and Ogun States, respectively) of the respondents were males; the mean age of the respondents was 47 years and 46 years in Osun and Ogun States, respectively. High (100.0% and 78.3%) Salmonella disease outbreaks were experienced in Osun and Ogun, respectively. Semi-intensive and intensive production systems are the predominant production methods in both states. The results further reveal that 56.7% and 70.0% of respondents in Osun and Ogun states had over 15 years of regular contact with extension services, respectively. However, the majority (83.3% and 91.7%) of Extension agents in Osun and Ogun states were knowledgeable about the Salmonella infection. The study concluded that for better adherence against disease outbreaks in poultry farms, monitoring and evaluation of all advisory services rendered should be done to ensure compliance. It is therefore recommended that there be improved biosecurity practices across the study location and adequate extension services that will enhance biosecurity measures and training to mitigate Salmonella outbreaks in poultry farms in the study area. Int. J. Agril. Res. Innov. Tech. 15(1): 115-126, June 2025